Changes in antioxidant activity, total phenolics and saponin content of different varieties of sesame (Sesamum indicum L.) seeds after roasting - Legacion, P. D. H. (Compendium of Human Ecology Researches in the Philippines, 2003)
Five varieties of sesame (Sesamum indicum L.) seeds were analyzed by spectrophotometer for changes in antioxidant activity, total phenolic content and saponin content of the seeds during cooking. The antioxidant activity, measured as reducing power, varied from 33.20% T to 41.70% T. 'Among them, black sesame seeds had the highest (34.70%T) while white sesame seeds had the lowest (38.25%T). The total phenolic content of sesame seed samples ranged from 0.35 to 1.31 mg/g. On the average, black sesame seeds had the highest total phenolic content (0.989 mg/g) while white sesame seeds had the lowest (0.683 mg/g). The saponin content of sesame seeds ranged from 0.04 to 0.26mg/g. White sesame seeds on the average had the highest saponin content (0.238mg/g) while black sesame seeds had the lowest (0.075 mg/g). Compared to raw sesame seeds, roasted sesame seeds had lower antioxidant activity (34.82%T), total phenolic content (0.509 mg/g), and saponin content (0.123 mg/g). Generally, the antioxidant activity and total phenolic content were higher in varieties with darker pigments while the opposite is true for saponin content. Roasting may have promoted degradation of the phenolic compounds in sesame seeds thereby significantly decreasing the antioxidant activity, total phenolic content, and saponin content of different varieties of sesame seeds.